Body Composition in Crohn's Disease and Ulcerative Colitis: Correlation with Disease Severity and Duration. (31st October 2017) - Yadav, Dawesh P.; Kedia, Saurabh; Madhusudhan, Kumble Seetharama; Bopanna, Sawan; Goyal, Sandeep; Jain, Saransh; Vikram, Naval K.; Sharma, Raju; Makharia, Govind K.; Ahuja, Vineet
Abstract : Background . Results on body composition in Crohn's disease (CD) and ulcerative colitis (UC) have been heterogeneous and are lacking from Asia. Present study assessed body composition in CD/UC and correlated it with disease severity/duration. Methods . Patients of CD/UC following between Dec 2014 and Dec 2015 who consented for bioimpedance analysis for body fat measurement were included. Lean mass and fat-free mass index (FFMI) were calculated with standard formulae. Visceral fat area (VFA), subcutaneous fat area (SCA), and visceral to subcutaneous fat ratio (VF/SC) were evaluated in CD patients on abdominal CT. Results . Lean mass in CD (n = 44, mean age: 41.2 ± 15.8 years, 73% males) was significantly lower than UC (n = 53, mean age: 33.2 ± 11.2 years, 68% males; 44.2 ± 7.8 versus 48.3 ± 8.4 Kg, p = 0.01 ). In both UC/CD, disease severity was associated with nonsignificant decline in BMI (UC: 22.1 ± 4.9 versus 20.2 ± 3.2 versus 19.9 ± 3.2 kg/m 2, p = 0.23 ; CD: 22.1 ± 4.2 versus 19.9 ± 2.3 versus 19.7 ± 4.2 kg/m 2, p = 0.18 ) and fat mass (UC: 10.9 ± 8.9 versus 8.1 ± 5.9 versus 5.7 ± 3.6 kg, p = 0.14 ; CD: 11.2 ± 7 versus 7.9 ± 4.4 versus 7.2 ± 5.9 kg, p = 0.16 ), and disease duration was associated with significant decline in FFMI (p < 0.05 ). In CD, disease severity was associated with nonsignificant decline in SCA and increase in VF/SC. Conclusions . CD patients have lower lean mass than UC. Body fat decreases with increasing disease severity and fat-free mass decreases with increasing disease duration in both UC/CD.